Role of Butyrate, a Gut Microbiota Derived Metabolite, in Cardiovascular Diseases: A comprehensive narrative review - Amiri, Parichehr; Hosseini, Seyed Ahmad; Ghaffari, Samad; Tutunchi, Helda; Ghaffari, Shamsi; Mosharkesh, Erfan; Asghari, Samira; Roshanravan, Neda (Frontiers in Pharmacology, 2022)
Cardiovascular diseases (CVD) are the major cause of death worldwide. Recently, new roles for intestinal microbiota in the pathology and treatment of CVD have been proposed. Butyrate, a bacterial metabolite, is synthesized in the gut and performs most of its functions there. However, researchers have discovered that butyrate could inter to the portal vein and interact with various organs. Butyrate exhibits a broad range of pharmacological activities, including microbiome modulator, anti-inflammatory, anti-obesity, metabolic pathways regulator, anti-angiogenesis, and antioxidant. In this article, we review evidence supporting a potential therapeutic role for butyrate in CVD and the mechanisms and pathways involved in the cardioprotective effects of butyrate from the gut and circulation to the nervous system. In summary, although butyrate exhibits a wide variety of biological activities in different pathways including energy homeostasis, glucose and lipid metabolism, inflammation, oxidative stress, neural signaling, and epigenetic modulation in experimental settings, it remains unclear whether these findings are clinically relevant and whether the molecular pathways are activated by butyrate in humans.